2019
DOI: 10.1016/j.polymer.2018.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Low-density PMMA/MAM nanocellular polymers using low MAM contents: Production and characterization

Abstract: Low-density nanocellular polymers based on PMMA/MAM blends are produced. • Low MAM copolymer contents, as low as 0.1 wt%, are used to produce such materials. • The physical mechanisms that allow this reduction of the density are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…PMMA/MAM being a good model system, a huge collection of experiments on batched-foamed PMMA/MAM structured blends was published varying wt% MAM (0.1 to 20 wt%), P saturation , T saturation , ∆P/dt, one-step vs. two-step foaming, T foaming . All works show that density is accessible between 1 and 0.25•10 3 kg•m −3 , mean pore diameter between several tens of micrometers to 0.1 µm, exceptionally down to 50 nm (thanks to hard low temperature saturation conditions) [39,81,89,101,102].…”
Section: Saturation Timementioning
confidence: 99%
“…PMMA/MAM being a good model system, a huge collection of experiments on batched-foamed PMMA/MAM structured blends was published varying wt% MAM (0.1 to 20 wt%), P saturation , T saturation , ∆P/dt, one-step vs. two-step foaming, T foaming . All works show that density is accessible between 1 and 0.25•10 3 kg•m −3 , mean pore diameter between several tens of micrometers to 0.1 µm, exceptionally down to 50 nm (thanks to hard low temperature saturation conditions) [39,81,89,101,102].…”
Section: Saturation Timementioning
confidence: 99%
“…The blend of poly(methyl methacrylate)-poly(butyl acrylate)-poly(methyl methacrylate) (MAM) copolymer with PMMA [33][34][35][36] was proved recently to allow reaching relative densities of 0.23 and cell sizes of 350 nm. [37] Another interesting system is the immiscible blend of PMMA with thermoplastic polyurethane (TPU) that results in a nanostructuration of the TPU phase, as shown by Wang and coworkers. [19] Using a two-step gas dissolution foaming method with an extra cooling step, they obtained a very low-density nanocellular polymer with a relative density as low as 0.125, while the cell size was only 205 nm.…”
Section: Introductionmentioning
confidence: 99%
“…11 Sputter coater SDC 005 of Balzers Union (Liechtenstein). 12 Scanning electron microscope QUANTA 200 FEG of Thermo Fisher Scientific (USA). 13 At least 200 cells were analysed from multiple micrographs per foamed sample.…”
Section: Open Cell Contentmentioning
confidence: 99%
“…Measurements of D at temperatures and pressures typical for solid-state nanofoaming of PMMA by CO2 are available in the literature as follows. Guo and Kumar [28] measured D based on desorption measurements and found that D ranges from 12 2…”
Section: Mass Conservationmentioning
confidence: 99%
See 1 more Smart Citation